The Motivation of Poor Community in Using Mobile Phone: An Effort to Improve Quality of Life - Setyowardhani, Hapsari (UI Scholars Hub, 2021)
The general objective of this research is to determine the primary motivation of the poor in the use of mobile telephone. The data collection was conducted by selecting 300 respondents which have income below minimum regional wage (or Upah Minimum Regional/UMR), living in Jakarta, Bogor, Depok, Tangerang,or Bekasi, and have at least one person as dependants.This study found that in general, the impact of mobile phone use on overall life quality is affected by perception of mobile phone impact on social life, love life, and financial life.There are different impact of mobile phone use, affected by perception of benefits and costs of mobile phone use in social life, leisure life, family life, health and safety life, love life, work life, and financial life.